2012
DOI: 10.2478/s11536-012-0057-1
|View full text |Cite
|
Sign up to set email alerts
|

Association between body mass index, body fat per cent and muscle power output in soccer players

Abstract: AbstractThe objectives of this study were to examine (a) the prevalence of overweight/obesity, (b) the relationship between body mass index (BMI) and body fat percent (BF), and (c) the association between BMI, BF and power output in adult male soccer players. Members of competitive soccer clubs (n=169, aged 22.7±4.2yr) were examined for anthropometric characteristics and body composition, and performed the physical working capacity in heart rate 170 min−1 test (PWC170), a force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
14
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 20 publications
(28 reference statements)
0
14
0
2
Order By: Relevance
“…A study that investigated the correlation of body composition and power output by a cycle ergometer showed that the power output in the high body fat group was lesser than that in the low body fat group. 24 Regarding handball players, it reported that body fat has a negative effect on power output. 25 In our study, although no significantly correlation was observed with performance test and body fat, physical performance was positively correlated with the physical characteristics of body mass, upper limb length, chest girth, waist girth, hip girth, calf girth, arm lean body mass, leg lean body mass, trunk lean body mass, total lean body mass, and arm BMC in both canoe and kayak paddlers.…”
Section: Discussionmentioning
confidence: 99%
“…A study that investigated the correlation of body composition and power output by a cycle ergometer showed that the power output in the high body fat group was lesser than that in the low body fat group. 24 Regarding handball players, it reported that body fat has a negative effect on power output. 25 In our study, although no significantly correlation was observed with performance test and body fat, physical performance was positively correlated with the physical characteristics of body mass, upper limb length, chest girth, waist girth, hip girth, calf girth, arm lean body mass, leg lean body mass, trunk lean body mass, total lean body mass, and arm BMC in both canoe and kayak paddlers.…”
Section: Discussionmentioning
confidence: 99%
“…Previous other studies have also reported significant and strong inverse relationship. 17,20,21 We did not observe any significant correlation between physical activity and BMI. Goel et al, Preto et al also didn't found any association between physical activity and BMI in their study.…”
Section: Discussionmentioning
confidence: 53%
“…In addition to the body weight difference among positions, there is a difference in body composition between sexes; additionally, fat-free mass has higher correlation with power, since force is more correlated to fat-free mass than to total body mass 28 .…”
Section: Discussionmentioning
confidence: 99%